Defining and Describing the Contemporary Memory Laws - Tomczak, Marcin (Sensus Historiae, 2019)
Memory laws understood as a type of regulation aimed at honouring or comme-morating certain events and heroes from the past are an interesting example of relations between law and history. The concept of memory laws is getting more and more familiar in Poland, but still, there are not many texts on this problem in Polish. Some parties in Europe (and in the world) are trying to introduce the so-called “memory police” and are using legislative competences to enhance the importance of their own vision of history. Therefore, the aim of this text is to define memory laws (including “soft” and “hard” memory laws) and to describe examples of memory laws from Poland, Europe and countries in other continents.